Fundamentals of Electrolytes for Solid-State Batteries: Challenges and Perspectives - Wang, Liguang; Li, Jun; Lu, Guolong; Li, Wenyan; Tao, Qiqi; Shi, Caihong; Jin, Huile; Chen, Guang; Wang, Shun (Frontiers in Materials, 2020)
Compared with traditional lithium-ion systems, solid-state batteries could achieve high safety and energy density. Although great improvements have been made, especially in solid-state electrolyte, fundamental challenges still remain in the solid-state systems in terms of chemistry and mechanics. This review summarizes the fundamental issues in solid-state batteries with a focus on three critical phenomena: (i) the principles of developing high ionic conductors, (ii) structural evolution at chemically unstable electrolyte-electrode interfaces, and (iii) the effects of manufacturing solid-state batteries, including electrode, electrolyte design. The future perspectives are also outlined to guide the development of solid-state batteries.